Conceptualising and Effecting Good Outcomes in Foster Care:an exploration of the research literature - Wilson, Kate; Sinclair, Ian; Taylor, C.; Pithouse, A.; Sellick, C. (Policy Press, 2004)
On any one day over 75,000 children are looked after by local authorities in the UK. Numerically the most important form of provision for these looked after children is foster care. This caters for about 60% of those looked after at any one point in time. This review is about its outcomes.